The Relation between the Red Sea Trough and Heavy Precipitation in Iran - Sohrab Ghaedi; Saeid Movahedi; Abolfazl Masoodian (جغرافیا و پایداری محیط)
In cold and transition seasons, a surface trough is forms over the Red Sea which can affect its neighbor regions. At the closest distance, the Red Sea is about 1500 km distant from Iran, which in synoptic scale is not too distant. Regarding the direction of large scale atmospheric streams, this trough can have some influences over Iran’s climate. In this research the impact of Red Sea Trough on the heavy precipitations of Iran was studied. The analysis of surface level maps indicated that out of 30 cases of heavy precipitations of Iran in the rank order (mean precipitation), 17 cases are related to the Red Sea Trough. Geopotential height maps in the middle level of atmosphere also show the simultaneous existence of middle trough at the time of precipitations in Iran with the Red Sea Trough. Three cases of these precipitations were analyzed. Moisture flux convergence maps at the time of the three heavy precipitations indicate the transmission of humidity from Arabian Sea toward Red Sea. Then this humidity through the impact of upward motions affected by middle level trough over Red Sea ascends and flows towards the eastern regions of this sea including Iran and, consequently, causes heavy precipitations. These heavy precipitations affect mostly south and south western s regions of Iran.